Unravelling the visible light-assisted catalytic prowess of an n–n type In2S3/CeO2 Z-scheme heterojunction towards organic and inorganic water pollution mitigation. (15th February 2021) - Murugalakshmi, M.; Jones, B. Filip; Mamba, G.; Maruthamani, D.; Muthuraj, V.
Abstract : The exploitation of visible light active photocatalysts for the removal of various pollutants has been given tremendous consideration in water and wastewater treatment. Abstract : The exploitation of visible light active photocatalysts for the removal of various pollutants has been given tremendous consideration in water and wastewater treatment. Herein, a novel In2 S3 /CeO2 n–n type heterojunction photocatalyst was successfully synthesized by a two-step method involving hydrothermal synthesis and subsequent ultrasonic treatment to couple In2 S3 with CeO2 (5, 10 and 15 wt%). The as-synthesized samples were characterized extensively using analytical techniques such as XRD, UV-vis-DRS, SEM-EDX, TEM, BET, PL, EIS and XPS to examine the chemical composition, phase structure, morphology and photo-chemical characteristics of the materials. Subsequently, the In2 S3 /CeO2 nanostructures were employed in the degradation of oxytetracycline (OTC) (10 mg L −1 ) and reduction of Cr(vi ) (50 mg L −1 ) in aqueous solutions, upon exposure to visible light. Under optimised experimental conditions, the nanocomposite constituting 10 wt% CeO2 (In2 S3 /10 wt% CeO2 ) showed the highest activity, reaching 87.9% OTC degradation and 97.5% Cr(vi ) reduction after 60 min and 40 min of visible light irradiation, respectively. The nature and contribution of active species in the photocatalytic process were revealed through radical scavenging studies. Finally, a plausible band structure, charge separation and transfer mechanism were crafted to illustrate the synergy between In2 S3 and CeO2 which led to improved degradation kinetics. This work demonstrated a simple route for improving the visible light-mediated activity of In2 S3 by coupling with CeO2 and the potential versatility of the composite material for the removal of both organic and inorganic pollutants from water.